FAMILIAL MEDITERRANEAN FEVER: THE REVIEW OF EULAR GUIDELINES, 2016 - M. T. Vatutin; G. S. Smyrnova; A. El-Khatib (SINAPS LLC, 2016)
Recommendations for the management of familial Mediterranean fever are reflected in presented translation of new international guidelines (EULAR, 2016)